Diversidade genética, fatores de virulência e perfis de susceptibilidade a antimicrobianos de isolados de Escherichia coli provenientes do útero, da boca e das fezes de cadelas com piometra - Agostinho, Juliana Maria Avanci [UNESP] (2013)
Canine pyometra is a disease characterized by the inflammation of the uterus with accumulation of purulent discharge, affecting mainly adult animals. Occurs in the luteus phase of the estrus cycle in result of hormone alterations and generally is associated with bacterial infections. It is recognized as one of the main causes of disease and death in the bitch and Escherichia coli is the major pathogen associated with this disease. The aim of this study was to research, isolation and identification of Escherichia coli strains from intrauterine contents, mouth and feces of bitches diagnosed with pyometra, studying the prevalence of uropathogenic virulence factors genes in strains isolated, still testing the genetic similarity among strains isolated from intrauterine contents and mouth and evaluate the susceptibility in vitro of the isolated bacteria to 12 antimicrobial drugs. Seventy E. coli strains, 25 from intrauterine contents, 26 from mouth and 19 from feces isolated from six bitches were examined by PCR. Among the strains 67 (95.7%) were positive for fim, 19 (27.1%) were positive for iss, 18 (25.7%) were positive for hly, 13 (18.5%) were positive for iuc and 12 (17.1%) were positive for usp. Multiple antimicrobial resistance was detected for cephalothin (68.0%), nalidixic acid (56.0%) and ampicillin (56.0%) among the pyomera E. coli isolates. Multidrug resistance was found in 12 (48.0%) of the isolates from pyometra, in 22 (84.6%) of the isolates from mouth and in 14 (73.6%) of the isolates from feces...